Global Existence and Long-Time Behavior of Solutions to the Full Compressible Euler Equations with Damping and Heat Conduction in ℝ3 - Yunshun Wu; Yong Wang; Rong Shen (Advances in Mathematical Physics)
We study the Cauchy problem of the three-dimensional full compressible Euler equations with damping and heat conduction. We prove the existence and uniqueness of the global small HNN≥3 solution; in particular, we only require that the H4 norms of the initial data be small when N≥5. Moreover, we use a pure energy method to show that the global solution converges to the constant equilibrium state with an optimal algebraic decay rate as time goes to infinity.